Teachers’ beliefs about English teaching – learning process in online classes. - Araque Vizcaíno, Santiago Alexis (2022)
The main objective of this qualitative case study was to explore the teachers´ beliefs about English teaching – learning process in online classes at Technical University of Cotopaxi majoring pedagogy of national and foreign languages. The participants in this study were four teachers who taught the subject of English. For data collection, a semi-structured interview guide was applied to the teachers. A bottom-up approach was applied to analyze the beliefs of the English teachers. A by-hand analysis was used to transcribe, encode and classify the information data, in this way four categories were obtained (Teaching-learning component in virtual mode, teacher role in virtuality, student role in virtuality and the main components of the learning process instruction). The results provide an overview of the teachers' beliefs about the teaching-learning process in online English classes. Teachers had to implement new strategies and methods, such as the use of digital platforms and technological tools to create a good academic environment to motivate students to achieve their academic goals. On the other hand, they stated that they faced problems such as the lack of technological devices, poor internet connection and the students' lack of willingness to learn. In addition, it was evident that the role of the teacher and the student was fundamental in the teaching-learning process, as the teachers were the ones who guided the students to transform the information into knowledge.